Advancement of the Creative Economy by Training in the Production of Economically Valuable Creative Products Derived from Banana Fronds - Sareethi Gotale (Community Service Akseprin Journal, 2025)
Banana fronds, which are generally considered agricultural waste, have substantial potential to be processed into creative products with high economic value. Despite Indonesia's abundance of natural resources, such as banana trees, the use of banana leaves remains limited. This article examines ideas for developing the creative economy through training aimed at enhancing the economic worth of creative items derived from banana fronds. This project seeks to ascertain the potential of banana fronds, develop effective training modules, and evaluate the effects of training on community skill enhancement, innovative product development, and revenue augmentation. The employed study methodology is participatory action research (PAR), which engages local communities through problem identification, action planning, training execution, and ongoing evaluation. Research indicates that extensive training encompassing raw material processing, product design, natural dyeing methods, and marketing strategies can substantially convert banana fronds from waste into economic resources. Product developments, including bags, caps, storage boxes, and domestic decorations crafted from banana fronds, demonstrate market appeal and the potential for the advancement of a community-based creative economy. This article aids in the design of community empowerment initiatives and the advancement of a circular economy